Structural and functional comparison of the persistent and resolved amblyopia - Tugcu, Betul; Araz-Ersan, Bilge; Erdogan, Ezgi Tuna; Tarakcioglu, Hatice; Coskun, Cigdem; Yigit, Ulviye; Karamursel, Sacit (Documenta ophthalmologica, 2014)
Purpose To assess structural or functional differences of the retina among subjects with persistent and resolved amblyopia. Methods Fourteen eyes with persistent amblyopia that did not reach normal visual acuity (VA) levels (≤0.1 LogMAR) despite amblyopia treatment, 18 eyes with resolved amblyopia, and 16 eyes of 16 normal subjects were included. All subjects underwent optical coherence tomography (OCT), pattern visual evoked potential (PVEP), and pattern electroretinography (PERG) evaluation. Results There was no significant difference in foveal thickness, foveal volume, macular volume, ganglion cell layer thickness, and total and sectorial retinal nerve fiber layer measurements among three groups ( p > 0.05). Foveolar thickness was significantly increased in both resolved and persistent amblyopia groups compared with the control group ( p = 0.031). However, there was no difference between amblyopic groups ( p = 0.98). Although, in the PVEP study, N75 implicit time was found significantly prolonged in both amblyopia groups ( p = 0.046), there were no significant differences in P100 implicit time and amplitude among the groups ( p > 0.05). PERG amplitude of the persistent group was significantly lower than that of the control group ( p = 0.003). There were no significant differences in P50, N95 implicit times among groups ( p > 0.05). Conclusions In our study, the only significant difference between persistent and resolved amblyopia groups was the initial VA. Neither OCT nor electrophysiological examinations were found to be useful in order to explain why some cases were resistant to the treatment for amblyopia.